Omnichannel Marketing Strategy and Its Influence on Purchase Decisions in Culinary MSMEs in a Metropolitan City, East Java - Indah Datin Nadliroh; Ayu Rachmawaty (JOURNAL KOPERASI DAN MANAJEMEN, 2026)
Purpose – This study aims to investigate the implementation of omnichannel marketing strategies and their impact on consumer purchase decisions among culinary Micro, Small, and Medium Enterprises (MSMEs) in Surabaya, East Java, Indonesia. Specifically, the study examines the effects of channel integration, personalization, and consistency on customer experience and purchase decisions, as well as the mediating role of customer experience and the moderating role of brand trust. Design/methodology/approach – This study employed a quantitative research design using a survey questionnaire distributed to 250 customers of culinary MSMEs in Surabaya that utilize multiple sales channels, including physical stores, Instagram, GoFood, and GrabFood. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the hypothesized relationships, including the mediation effect of customer experience and the moderation effect of brand trust. Findings – The results indicate that omnichannel marketing strategies, characterized by channel integration, personalization, and consistency, have a significant positive effect on customer experience. Furthermore, customer experience significantly mediates the relationship between omnichannel marketing strategy and consumer purchase decisions. These findings indicate that integrated and consistent customer interactions across multiple channels can enhance customer experiences and ultimately encourage purchase decisions. Research limitations/implications – This study is limited to culinary MSMEs and their customers in Surabaya, which may restrict the generalizability of the findings to other sectors, regions, or types of MSMEs. The cross-sectional design also limits the ability to capture changes in consumer behavior over time. Future research could examine other MSME sectors, geographical areas, and additional variables such as customer engagement, perceived value, digital literacy, and customer loyalty. Originality/value – This study contributes to the digital marketing literature by integrating omnichannel marketing, customer experience, and brand trust into a unified framework for explaining consumer purchase decisions in the MSME context. Its originality lies in examining customer experience as a mediating mechanism and brand trust as a moderating factor within an omnichannel marketing framework.